Fibroblast growth factor receptors across urothelial carcinoma landscape. Issue 4 (July 2020) - Ertl, Iris E.; Shariat, Shahrokh F.; Mostafaei, Hadi; Ilijazi, Dafina; Loriot, Yohann
Abstract : Purpose of review: Fibroblast growth factor receptor (FGFR) signalling, especially induced by FGFR3, is a crucial factor in the pathogenesis of urothelial carcinoma and was therefore extensively studied over the last decades. In this review, we summarize the most relevant findings of the past two years. Recent findings: Recent studies support the concept that FGFR3 mediates a pathway of urothelial carcinogenesis associated with low malignant potential. FGFR3 may represent a highly accurate biomarker for diagnosis and prediction of recurrence, progression or therapy response. The pan FGFR-inhibitor erdafitinib was recently approved for urothelial carcinoma, whereas several other FGFR-targeted drugs are currently undergoing clinical trials. Summary: Numerous recent studies focus on the role of FGFR3 in different urothelial carcinoma subtypes and its potential clinical application as noninvasive biomarker, as well as therapeutic target.